The Implementation of Islamic Economic Values in Islamic Religious Education Learning for Strengthening Sharia Entrepreneurship Character - Riza Mukhamad Niam; Novita Eka Paradina; Isti Fajri Khairunnisa (The Future of Education Journal, 2023)
This study examines the implementation of Islamic economic values in Islamic Religious Education (IRE) as a strategy for strengthening Sharia entrepreneurial character at the Islamic Institute of Yasni Bungo (IAI Yasni Bungo), Jambi, Indonesia. The study aims to describe the integration of Islamic economic values into the curriculum and instructional practices of Islamic Religious Education, analyze their impact on the development of Sharia-based entrepreneurial character, and identify the supporting and inhibiting factors influencing their implementation. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis involving IRE lecturers, students, and managers of campus business units. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings reveal that the integration of Islamic economic values in Islamic Religious Education is carried out through the incorporation of the principles of tawhid (monotheism), justice, maslahah (public benefit), and muamalah ethics into courses on morality, Islamic jurisprudence, and the history of Islamic civilization. Learning activities are enriched through project-based learning, Sharia business simulations, and entrepreneurship mentoring programs. This implementation contributes significantly to strengthening students’ Sharia entrepreneurial character, particularly in terms of transaction honesty, awareness of halal and haram principles, economic independence, and halal product innovation. Supporting factors include lecturers’ commitment, a flexible curriculum, and a supportive campus ecosystem, whereas inhibiting factors involve limited practical literature, heavy academic workloads, and insufficient long-term business mentoring. The study recommends strengthening collaboration among Islamic Religious Education lecturers, Sharia business practitioners, and university business incubators, as well as developing measurable assessment instruments for entrepreneurial character. These findings provide both empirical and conceptual contributions to the development of Islamic Religious Education curricula that are responsive to contemporary economic challenges.